Regulation on cross-border tourism between China and Kazakhstan: dilemmas & reflection - Yu-qin, Liu; Wen-Hao, Liu; Lin, Dong (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
As China’s “Belt and Road” initiative and Kazakhstan’s “Bright Road” initiative become more and more popular, cooperation between China and Kazakhstan is booming, and the legal system is becoming more and more perfect. However, as part of China-Kazakhstan service trade, the development of cross-border tourism is slightly sluggish under such a background. This article starts with the dilemma of the construction of the cross-border tourism industry and the corresponding legal system between China and Kazakhstan and presents the dilemma. Then, the reasons for the dilemma are analyzed from the perspectives of market orientation, international environment and geographical factors, and implementation issues. Furthermore, this article attempts to construct a new paradigm for the development of the legal regulation system of cross-border tourism between China and Kazakhstan. From the perspective of what the two governments can do, it is advocated to sign a national-level legal agreement or memorandum on bilateral tourism cooperation between China and Kazakhstan, and jointly plan and promote tourism routes. And countermeasures are proposed from different perspectives of the implementation of supporting systems by the administrative system and the guidance of private development. With the help of China’s unswerving expansion of all-around opening up, it is hoped that the tourism legal systems of the two countries can be improved.